The Offshore Centres in Southeast Asia - Rosińska, Magdalena (Centra offshore w Azji Południowo-Wschodniej, 2010)
The globalization of economy way has changed relations between native tax systems. It gives an option to relocate business into offshore centres and tax havens (countries, where terms to register and manage activity, because of their tax legislation, are profitable), where they can be registered and make tax duties in minimum range (it depends on the type of offshore centre). Because of lots of privileges companies are looking for places, where their activity can be profitable. Those privileges are for example: temporal transfer of incomes to tax haven for changing the deadline to pay the tax, cooperation with an offshore company which is a middleman in selling articles abroad or using international agreements to avoid double taxes.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 134, s. 131-145
Keywords: liberalization of capital flows; tax havens; offshore centres; global tax legislation